Opportunities for the Application of 3D Printing in the Critical Infrastructure System - Grzegorz Budzik; Krzysztof Tomaszewski; Andrzej Soboń (Energies, 2022)
The present article presents an analysis of the potential application of 3D printing in the critical infrastructure system. An attempt has been made to develop case studies for selected critical infrastructure areas, particularly with reference to the area of energy supply. The need for 3D printing applications is identified based on expert research in the energy industry. It identifies the application schemes determined by the technical and logistical possibilities associated with 3D printing in its broadest sense. A review of additive technologies with a view to their application in selected phases of critical infrastructure operation, including in crisis situations, is also carried out. Furthermore, a methodology for incorporating 3D printing into the existing critical infrastructure system is proposed. As a result, the following research hypothesis is adopted: the use of 3D printing can be an important part of measures to ensure the full functionality and efficiency of critical infrastructures, particularly in crisis situations.